Genetic resources for stem rust resistance in cultivated and wild tetraploid wheats - Olivera P.D.; Yue J. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
New emerging races of Puccinia graminis f. sp. tritici are a serious threat to durum and bread wheat production worldwide because of their virulence on many cultivars and rapid spread. Our research objective was to indentify new sources of stem rust resistance in cultivated and wild tetraploid wheats that could be utilized in durum breeding. We characterized 3500 durum (T. turgidum ssp. durum) and 360 emmer wheat (T. turgidum ssp. dicoccum) accessions for stem rust resistance in multiple field and seedling evaluations. Search for resistance through seedling evaluation was also conducted in 1770 accessions of wild and cultivated T. turgidum ssp. and Aegilops ssp. Accessions exhibiting a high level of stem rust resistance to TTKSK (or Ug99 race) and other races were observed in all the species evaluated. Studies on the inheritance of TTKSK resistance revealed that resistance was conferred mostly by one and two genes. Our studies concluded that wild and cultivated tetraploids are a rich source of resistance to race TTKSK, and may contribute with novel stem rust resistance genes.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)